Grazing management in an integrated crop-livestock system: soybean development and grain yield (Revista Ciência Agronômica, 2015)
Grazing livestock in integrated crop-livestock systems can cause impacts in the subsequent crop cycle.Aiming to investigate how grazing could affect soybean, the 9th crop cycle of a pasture/soybean rotation was assessed.Treatments were grazing intensities (10, 20, 30 and 40 cm of sward height) applied since 2001 in a mixed of oat andannual ryegrass; and an additional no grazing area as control. Treatments were arranged in a completely randomizedblock design with three replicates. Grazing affected soybean population and the mass of individual nodules (P0.05). Soybean yield showed differences amongtreatments, but no difference was found between grazed and non-grazed areas. Grazing intensities impact the coverageand frequency of weeds (P>0.05). In conclusion, grazing intensity impacts different parameters of soybean yield anddevelopment, but only the grazing intensity of 10 cm can jeopardize the succeeding soybean crop.